Plant fruit extracts enhance the in vitro propagation of cowpea (Vigna unguiculata) on Murashige and Skoog media - Grace Markin; John S. Y. Eleblu; Jacqueline N. Amissah; Samuel Reynolds; Charline Soraru; Melanie S. Craze; Emma J. Wallington; Alison R. Bentley; Eric Y. Danquah (Plant Cell, Tissue and Organ Culture (PCTOC), 2023)
Cowpea ( Vigna unguiculata ) is a versatile legume with diverse nutritional and nutraceutical properties that serve as a food security and medicinal crop for millions of households across Africa. An efficient protocol was developed to propagate shoot tip and cotyledonary node explants from six cowpea breeding accessions in vitro on Murashige and Skoog (MS) basal media supplemented with either banana extract, coconut water, orange or tomato juice. Micropropagation performance was compared to MS medium supplemented with B5 vitamins. A total of 500 plantlets were obtained in vitro across treatments and MS basal media supplemented with tomato juice had the highest micropropagation performance (154 plantlets), followed by banana extract (112 plantlets), orange juice (107 plantlets), and coconut water (82 plantlets). Three accessions (AGRAC 216, TA, and Asontem) were found to be the most amenable to in vitro propagation using plant-derived extracts. Overall, this study successfully established that plant-derived extracts can support in vitro cowpea propagation in the absence of synthetic plant growth regulators.

Wheat root systems as a breeding target for climate resilience - Eric S. Ober; Samir Alahmad; James Cockram; Cristian Forestan; Lee T. Hickey; Josefine Kant; Marco Maccaferri; Emily Marr; Matthew Milner; Francisco Pinto; Charlotte Rambla; Matthew Reynolds; et al. (Theoretical and Applied Genetics, 2021)
In the coming decades, larger genetic gains in yield will be necessary to meet projected demand, and this must be achieved despite the destabilizing impacts of climate change on crop production. The root systems of crops capture the water and nutrients needed to support crop growth, and improved root systems tailored to the challenges of specific agricultural environments could improve climate resiliency. Each component of root initiation, growth and development is controlled genetically and responds to the environment, which translates to a complex quantitative system to navigate for the breeder, but also a world of opportunity given the right tools. In this review, we argue that it is important to know more about the ‘hidden half’ of crop plants and hypothesize that crop improvement could be further enhanced using approaches that directly target selection for root system architecture. To explore these issues, we focus predominantly on bread wheat ( Triticum aestivum L.), a staple crop that plays a major role in underpinning global food security. We review the tools available for root phenotyping under controlled and field conditions and the use of these platforms alongside modern genetics and genomics resources to dissect the genetic architecture controlling the wheat root system. To contextualize these advances for applied wheat breeding, we explore questions surrounding which root system architectures should be selected for, which agricultural environments and genetic trait configurations of breeding populations are these best suited to, and how might direct selection for these root ideotypes be implemented in practice.

Increasing erucic acid content through combination of endogenous low polyunsaturated fatty acids alleles with Ld-LPAAT + Bn-fae1 transgenes in rapeseed (Brassica napus L.) - Ujjal K. Nath; Jeroen A. Wilmer; Emma J. Wallington; Heiko C. Becker; Christian Möllers (Theoretical and Applied Genetics, 2009)